Two Main Cellular Components in Rheumatoid Arthritis: Communication Between T Cells and Fibroblast-Like Synoviocytes in the Joint Synovium - Tu, Jiajie; Huang, Wei; Zhang, Weiwei; Mei, Jiawei; Zhu, Chen (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that endangers the health of approximately 1% of the world’s population. Current RA medications on the market mainly include non-steroidal anti-inflammatory drugs, biological agents, and disease-modifying drugs. These drugs aim to inhibit the overactivated immune response or inflammation of RA, but they cannot cure RA. A better understanding of the pathogenesis of RA will provide a new understanding to search for RA targets and for drug development. The infiltration of T cells and hyper-proliferation of fibroblast-like synoviocytes (FLS) in the synovium of RA patients are significantly upregulated. Further, the abnormal activation of these two types of cells has been confirmed to promote development of the course of RA by many studies. This article systematically summarizes the regulation between T cells/FLS in RA synovial tissues, including one-way/mutual regulation and direct/indirect regulation between T cells and FLS, aiming to investigate the pathogenesis of RA from the perspective of mutual regulation between T cells and FLS and to provide new insights into RA research.